Synthesis of Antibacterial Coating Film Based on Eugenol-Allyl Eugenol Copolymer with Chitosan-Gelatin - Ngadiwiyana, Ngadiwiyana; Dzahabiyyah, Hana Putri; Ismiyarto, Ismiyarto; Sarjono, Purbowatiningrum Ria (Jurnal Kimia Valensi, 2024)
The development of coating film materials based on biopolymers and active antibacterial compounds has attracted attention in the food industries. Food packaging biopolymers can be increased antibacterial properties by adding compound modification of natural ingredients such as eugenol-allyl eugenol copolymer (PEAE). The aims of this study were to synthesize a coating film based on chitosan-gelatin with PEAE and test its antibacterial properties. PEAE synthesis was carried out by polymelirization reaction with the (BF3O(C2H5)2) as catalyst and characterized by FTIR, molecular weight, and solubility. Synthesis of chitosan-gelatin coating films with variations in PEAE concentration of 1.25%, 2.5%, and 3.75% and characterization includes FTIR, SEM, TS, E%, and contact angle. Antibacterial activity is carried out by the turbidimetry method. PEAE was synthesized with the results in the form of brown solids with 94.91% yield, molecular weight of 9,553.98 da, and the melting point of 95-98 °C. Chitosan-Gelatin films with the addition of PEAE produce a thin yellowish film, with a sequential decreased tensile strength, and the percentage value of extension increases with the increase in PEAE concentration. The best antibacterial activity in the film PEAE 2.5, with the percentage of inhibition of Staphylococcus aureus and Escherichia coli of 99.71% and 98.39% respectively.